2008
DOI: 10.1002/hed.20948
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of diagnostic upper node evaluation during (salvage) laryngectomy for supraglottic carcinoma

Abstract: Selective upper node dissection and inspection during laryngectomy reduced the need for an elective neck dissection with its morbidity in the clinically N0 neck. In addition, it selects the patients who need such extensive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…A total of 3 studies reported occult nodal metastases in hemidissected necks (unilateral and bilateral NDs), however, did not comment on whether they occurred in the contralateral neck. Pennings et al reported results based on patients who had lymph nodes at levels II and III visually and manually inspected intraoperatively; any suspicious lymph nodes were removed by selective upper node dissection, and if either inspection or dissection was positive for neck metastases a modified radical ND of levels I‐V was performed on the affected side . Using this method of intraoperative nodal inspection, the reported occult nodal positivity rate from this cohort (12.5%) was similar to the pooled result from our review, and the occult node occurred in the contralateral neck in only 1 of the 4 patients.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…A total of 3 studies reported occult nodal metastases in hemidissected necks (unilateral and bilateral NDs), however, did not comment on whether they occurred in the contralateral neck. Pennings et al reported results based on patients who had lymph nodes at levels II and III visually and manually inspected intraoperatively; any suspicious lymph nodes were removed by selective upper node dissection, and if either inspection or dissection was positive for neck metastases a modified radical ND of levels I‐V was performed on the affected side . Using this method of intraoperative nodal inspection, the reported occult nodal positivity rate from this cohort (12.5%) was similar to the pooled result from our review, and the occult node occurred in the contralateral neck in only 1 of the 4 patients.…”
Section: Discussionsupporting
confidence: 79%
“…The laryngeal subsite of recurrence was documented in 6 studies (290/1141, 25.4% of patients) that contained patients who were cN0 and received END (164 glottic, 81 supraglottic, 43 transglottic, 2 subglottic). Unilateral and/or bilateral ND was noted in 7 studies . The treatment categories are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This percentage was maintained in both a group that received neck dissection and in a group that was observed 14. Pennings et al examined the efficacy of upper node evaluation for salvage laryngectomy for supraglottic carcinoma and found a 19% overall occurrence of occult neck metastases: 6% for those receiving laryngectomy after radiotherapy and 24% for those receiving primary laryngectomy 7. Kligerman et al examined 76 patients with clinically T3/T4 N0 SCC of the larynx and found a 30% frequency of occult neck disease 15.…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques have been suggested for improving the decision‐making process regarding neck dissection in clinically N0 necks, including lymph node evaluation during laryngectomy 7. Guidance may be provided by preoperative imaging.…”
Section: Introductionmentioning
confidence: 99%